Tissue-Dependent Adaptations and Functions of Innate Lymphoid Cells - Murphy, Julia M.; Ngai, Louis; Mortha, Arthur; Crome, Sarah Q. (Frontiers in Immunology, 2022)
Tissue-resident immune cells reside in distinct niches across organs, where they contribute to tissue homeostasis and rapidly respond to perturbations in the local microenvironment. Innate lymphoid cells (ILCs) are a family of innate immune cells that regulate immune and tissue homeostasis. Across anatomical locations throughout the body, ILCs adopt tissue-specific fates, differing from circulating ILC populations. Adaptations of ILCs to microenvironmental changes have been documented in several inflammatory contexts, including obesity, asthma, and inflammatory bowel disease. While our understanding of ILC functions within tissues has predominantly been based on mouse studies, the development of advanced single-cell platforms to study tissue-resident ILCs in humans and emerging patient-based data is providing new insights into this lymphocyte family. Within this review, we discuss current concepts of ILC fate and function, exploring tissue-specific functions of ILCs and their contribution to health and disease across organ systems.